FRI0383 Laser speckle contrast imaging (LASCA) is a valid aid in the differential diagnosis of raynaud's phenomenon. (23rd January 2014) - Della Rossa, A.; d'Ascanio, A.; Cazzato, M.; Mosca, M.; Bombarderi, S.
Abstract : Background: Raynaud's phenomenon (RP) is a reversible vasospasm of the extremities that can occur either as an isolated symptom without underlying disorders (primary RP) or in association with another disorder or condition (secondary RP). Most cases of severe RP are associated with Connective tissue diseases (CTD). This symptom occurs in 90% of patients with systemic sclerosis and is often perceived as the most important clinical problem. RP is the clinical reflection of diffuse microvascular damage typical of the disease. Infact, according to the so called vascular hypothesis raised by LeRoy, microvascular involvement is pivotal for SSc pathogenesis and may be the direct trigger for the fibrotic process seen in this disease. Objectives: To assess digital blood flow in scleroderma (SSc) patients as compared to patients with primary Raynaud's phenomenon (PRP) and healthy subjects. To test if abnormalities in flow intensity and distribution could be useful in discriminating between healthy subjects and PRP and SSc patients. Methods: Skin blood flow in the dorsum of the digits was measured in 24 SSc patients, 20 patients with PRP (according to LeRoy criteria) and 20 healthy subjects. Cutaneous blood flow was measured throughout the experiments using a high frame rate laser speckle contrast imager (Pericam PSI system, Perimed, Jarfalla). Subjects were firstly acclimatized by getting them to rest at a constant temperature (22-24 °C) for 30 minutes. The basal recording lasted 5 minutes. 4 regions of interest (ROIs), corresponding to the dorsum of the second, third, fourth and fifth digit of the non-dominant hand were selected. Differences in blood flow between digits were recorded. Results: None of the healthy subjects, compared to 5 out of 20 PRP patients (25%) and 19 out 24 SSc patients (79%) showed a difference in the blood flow between digits higher than 20% (p<0.0001). This difference was not correlated with a history of digital ulcers nor with the appearance of new digital lesions in SSc subjects. The mean capillary density was significantly lower (4.2/mm vs 6.8/mm p<0.0001) in subjects with a difference between digits higher than 20% as compared with subjects in whom this difference was not noticed. Conclusions: Within Raynaud's phenomenon population, the presence of a strong difference in perfusion between digits could prove useful in the differential diagnosis and the early recognition of the secondary forms. References: LeRoy EC. Systemic sclerosis. A vascular perspective. Rheum Dis Clin North Am 1996; 22: 675-694. LeRoy EC, Medsger TA. Rayanud's phenomenon: a proposal for classification. Clin Exp Rheumatol 1992; 10 (5): 485-488. Roustit M, Millet C, Blaise S, Doufornet B, Cracowsky JL. Excellent reproducibility of laser speckle contrast imaging to assess skin microvascular reactivity. Microvasc Res, 2010 Dec 80 (3): 505-511. Disclosure of Interest : None Declared